2023
DOI: 10.2147/oajsm.s417612
|View full text |Cite
|
Sign up to set email alerts
|

Sports Physiology in Adolescent Track-and-Field Athletes: A Narrative Review

Abstract: The present study aimed to review the physiological aspects of adolescent track-and-field (TAF) athletes. A search of Scopus on 27/12/2022 using the syntax ABS (track-and-field) AND ABS (children) OR ABS (adolescent) showed 121 documents, and 45 were considered for further analysis. In addition, handsearching was conducted to identify Russian literature missing in Scopus. Differences were shown in performance characteristics among disciplines, especially between throwers and the other athletes. The sex differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Notably, recent research in road cycling indicated that the RAE might manifest until the U-15 categories, gradually diminishing as athletes reach the U-19 category [9]. Indeed, the end of puberty in males is likely to occur during the junior years (i.e., between 16 and 18 years old), implying discrepancies in anaerobic capabilities, while most female athletes might have already reached the term of that maturation period [32]. Considering long-term performance development, becoming physically and mentally stronger at a later age may hold greater importance, especially in the endurance disciplines [26].…”
Section: Additional Factors Affecting Successmentioning
confidence: 99%
“…Notably, recent research in road cycling indicated that the RAE might manifest until the U-15 categories, gradually diminishing as athletes reach the U-19 category [9]. Indeed, the end of puberty in males is likely to occur during the junior years (i.e., between 16 and 18 years old), implying discrepancies in anaerobic capabilities, while most female athletes might have already reached the term of that maturation period [32]. Considering long-term performance development, becoming physically and mentally stronger at a later age may hold greater importance, especially in the endurance disciplines [26].…”
Section: Additional Factors Affecting Successmentioning
confidence: 99%
“…Hence, an efficient selection or transfer of talent in track and field throwing events is unfeasible prior to this age due to the significant variations in growth spurts, physical traits, and training experiences during puberty that confer greater speed, strength, and size to adolescent athletes (Zhao and Zhao, 2023). The distinctive nature of the throwing motion results in marked differences in fitness characteristics when compared to other sports (Nikolaidis & Son'kin, 2023;Thorland et al, 1981). Therefore, studies of sports-specific characteristics are essential.…”
Section: Figurementioning
confidence: 99%
“…Scholars have progressively acknowledged the crucial significance of sport-specific anthropometric and physical measurement values in the realm of competency assessment [5,6]. Due to the specialized nature of the throwing motion, its fitness characteristics is significantly different from other sports [4,7], thus emphasizing the necessity of sport-specific characteristic studies. There have been some reports on the physiological and anthropometric characteristics of adult and elite athletes [8,9].…”
Section: Introductionmentioning
confidence: 99%